Efecto de la inclusión de β-glucanos en dieta sobre la Citometría hemática, ionogramas y aspartato amino Transferasa en juveniles de tilapia roja (Oreochromis mossambicus x Oreochromis niloticus) - Vistin García, Adrián Andrés (2021)
In Ecuador, tilapia adapts easily to different environmental environments and is one of the most important freshwater species, also worldwide. This research aimed to evaluate ionograms, hematic cytometry and glutamic oxaloacetic transaminase metabolic activity in juvenile red tilapia (Oreochromis mossambicus x O. niloticus) fed with additions of β glucans in diet. It was held at the El Vergel site, Valencia canton, Los Ríos Province; In the research, a completely randomized design (DCA) was used under controlled conditions for 56 days, for a total of 6 treatments (0, 1, 2, 3, 4 and 5% of β-glucan in diet) with three repetitions (plastic pools with 25 liters of water), a density of 15 juveniles / tanks was used. The variables were subjected to Duncan's multivariate test with P <0.05 of reliability. Hematic cytometry variables (hematocrit, erythrocytes, mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration), iron and sodium ionagrams were evaluated. and glutamic oxaloacetic transaminase enzymatic activity. The diets were subjected to bromatological analyzes. In the results, it was possible to identify the hematocrit responses, the mean was 30.33%, the erythrocytes had a mean of 1.00 M / uL; for these variables there was no significant difference. For the variable Mean Corpuscular Volume the mean was 93.49 fL, in the Mean Corpuscular Hemoglobin an average of 32 pg was observed and for the Mean Corpuscular Hemoglobin Concentration the mean was 34 g / dL, in the sodium ionograms a mean of 147.00 mmol / L and the iron ionogram showed a mean of 373 ug / dL; in these variables if statistical significance was observed. In the enzymatic activity of glutamic oxaláxetic transaminase the mean was 151 U / L, in this variable there was no significant difference. Key words: biostimulant, pelleted diets, hematocrits, iron, nutrition